2013
DOI: 10.1007/978-1-62703-523-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Activating the NLRP3 Inflammasome Using the Amyloidogenic Peptide IAPP

Abstract: In addition to several other extracellular substances, phagocytosis of amyloid-forming peptides can perturb cellular homeostasis, leading to activation of the cytoplasmic innate immune receptor NLRP3. Once triggered, NLRP3 forms an inflammasome complex that ultimately cleaves pro-IL-1β and pro-IL-18 into their mature, secreted forms. Here we describe a protocol by which one type of amyloidogenic peptide, islet amyloid polypeptide (IAPP, otherwise known as amylin) can be prepared and used to stimulate myeloid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In support of this, hIAPP aggregates have been shown to promote maturation of proIL-1β to IL-1β via activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome [46,47]. In addition, we recently showed that the inhibition of amyloid formation reduces islet IL-1β levels and Fas upregulation [7].…”
Section: Discussionmentioning
confidence: 80%
“…In support of this, hIAPP aggregates have been shown to promote maturation of proIL-1β to IL-1β via activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome [46,47]. In addition, we recently showed that the inhibition of amyloid formation reduces islet IL-1β levels and Fas upregulation [7].…”
Section: Discussionmentioning
confidence: 80%
“…Immediately prior to each experiment, IAPP was dissolved in 0.1 M acetic acid and diluted in culture medium. To assess amyloid fibril formation, IAPP aggregation was monitored by thioflavin T fluorescence (21). For examination of fibril formation by transmission electron microscopy (TEM), 3-l aliquots of IAPP prepared by dissolution at 100 M in distilled water and incubation at room temperature for 0 -16 h were adsorbed to glow-discharged carboncoated collodion film on copper grids.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, islet macrophages are the major source of hIAPPinduced IL-1β in islets, and islet macrophage depletion can improve hIAPP-induced islet dysfunction (7). Given that IAPP can deliver the two signals required for IL-1β secretion [9,10,23] and that anti-IL-1 therapy can improve beta cell function in patients with type 2 diabetes [12], here we asked whether IL-1 mediates hIAPP-induced islet dysfunction in vivo. We found that IL-1Ra markedly improved glycaemia and islet inflammation in a mouse model of islet amyloid formation and type 2 diabetes.…”
Section: Il-1ra Limits Islet Amyloid Formation In Lean A-hiappmentioning
confidence: 99%
“…While in vitro evidence suggests that interaction of hIAPP with macrophages induces release of cytokines such as IL-1β that at high local concentrations are known to cause beta cell dysfunction [10,23], it is likely that IL-1 also plays an important physiological role in regulating islet homeostasis. For example, low concentrations of IL-1β promote beta cell proliferation, and IL-1β knockout mice have impaired glucose tolerance and decreased islet Pdx1 expression [43].…”
Section: Il-1ra Limits Islet Amyloid Formation In Lean A-hiappmentioning
confidence: 99%